Transcriptomic Analysis and Functional Gene Expression in Different Stages of Gonadal Development of Macrobrachium rosenbergii - Zhenxiao Zhong; Guozhu Chen; Haihui Tu; Xinyi Yao; Xin Peng; Xuan Lan; Qiongying Tang; Shaokui Yi; Zhenglong Xia; Miaoying Cai; Guoliang Yang (Fishes, 2023)
In order to decipher the functional genes and reveal the molecular mechanism of gonadal development in Macrobrachium rosenbergii, a comparative transcriptome analysis was performed on the testes and ovaries at different developmental stages. A total of 146,537 unigenes with an N50 of 2008 bp and an average length of 1144 bp were obtained from the sequencing raw data via quality control and denovo assembly. Identification of differentially expressed genes (DEGs) showed that there were 339 and 468 DEGs among the different developmental stages of testes and ovaries, respectively, and 7993 DEGs between the testes and ovaries. The KEGG enrichment analysis identified 13 candidate pathways related to gonadal development, including insulin synthesis, oocyte maturation, and steroid biosynthesis, which were involved in biological processes such as regulation of hormone metabolism, sex cell proliferation and development, and amino acid metabolism. The DEGs related to the above pathways such as insulin-like growth factor 1 receptor (IGF1R), heat shock protein 90 (Hsp 90), and cyclooxygenase (COX) genes were highly expressed during yolk protein synthesis, indicating that these genes might be involved in yolk accumulation and oogenesis. Meanwhile, calmodulin (CaM) and other genes were highly expressed during spermatogenesis, suggesting that these genes might play an important role in spermatogenesis. Ten differentially expressed genes in the KEGG signaling pathway, including CRQ, COX, APP, Cdc42, Hsd17b12, Art-1, Hsp70, Hsp90, PRMT1, and GP, were selected for real-time quantitative PCR (RT- qPCR) to validate the transcriptome data, and the results showed that RT- qPCR obtained consistent results with the RNA-Seq data. The present findings provide new insights into the molecular regulation mechanism of gonadal development in M. rosenbergii.